A life decoded : my genome, my life - Venter, J. Craig (New York : Viking, 2007)
The story of the man who achieved one of the greatest feats of our era--the mapping of the human genome. After nearly flunking out of high school, Venter went to Vietnam, where the life and death struggles he encountered as a medic piqued his interest in science and medicine. In 1984 he joined the National Institutes of Health, introduced novel techniques for rapid gene discovery, and left in 1991 to form his own nonprofit genomics research center, where he sequenced the first genome in history in 1995. In 1998 he announced that he would successfully sequence the human genome years sooner, and for far less money, than the government-sponsored Human Genome Project would--a prediction he kept in 2001. The tale involves as much politics (personal and political) as science. He also describes the other startling projects he has conducted since.--From publisher description.
Writing my code -- University of death -- Adrenaline junkie -- Starting over in Buffalo -- Scientific heaven, bureaucratic hell -- Big biology -- TIGR cub -- Gene wars -- Shotgun sequencing -- Institutional divorce -- Sequencing the human -- Mad magazine and destructive businessmen -- Flying forward -- The first human genome -- The White House, June 26, 2000 -- Publish and be damned -- Blue planet and new life.
Includes bibliographical references (p. [361]-374) and index.
Keywords: Venter, J. Craig; Venter, J. Craig; Geneticists -- United States -- Biography; Human gene mapping -- History; DNA -- Analysis -- History; Genetics -- United States -- Personal Narratives; Chromosome Mapping -- United States -- Personal Narratives; Genome, Human -- United States -- Personal Narratives; Sequence Analysis, DNA -- United States -- Personal Narratives